Cross-Dialect Irish Prosody: Linguistic Constraints on Fujisaki Modelling - GOBL, CHRISTER; NI CHASAIDE, AILBHE (My University, 2008)
We describe here our approach to quantifying cross-dialect differences in Irish Gaelic, using the Fujisaki model. The basic principle is that the way in which the modelling is carried out respects a parallel linguistic (AM) analysis. The aims are: (1) to ensure that our modelling strategies permit a reliable cross-dialect comparison, (2) that the model-derived measurements can be related to meaningful linguistic dimensions and (3) that the analysis forms the basis for multidialect synthesis.
Proceedings of the 9th International Conference on Spoken Language Processing, INTERSPEECH 2008
PUBLISHED
Brisbane, Australia
Keywords: Irish Gaelic, Fujisaki model, speech synthesis.